Adenoid Cystic Carcinoma of the Submandibular Gland, Locoregional Recurrence, and a Solitary Liver Metastasis More Than 30 Years Since Primary Diagnosis - A. Coupland; A. Sewpaul; A. Darne; S. White (Case Reports in Surgery)
Adenoid cystic carcinoma (ACC) is a relatively rare tumour of the salivary glands, accounting for approximately 5%–10% of all salivary gland tumours. An important feature of ACCs is the long clinical course with a high rate of distant metastases. The preferential sites of metastases are the lung and bone, followed by the brain and liver. Most liver metastases are derived from nonparotid ACCs, and the presentation is often related to local recurrence or metastases to other organs. Solitary metastases to the liver are rare and optimal management is unknown. We present the case of a metastatic ACC to the liver with primary disease presentation at a young age. We discuss our management and other potential treatment modalities.